Corporate social responsibility: ‘the impact of corporate community investment on standard chartered bank (SCB)’/ Nadia Prima Nasir - Prima Nasir, Nadia (Faculty of Business and Management, 2010)
Corporate social responsibility (CSR) initiatives have experienced unprecedented growth in the last few years. In developing country like Malaysia, the importance of CSR has been recognized by most corporations to ensure long-term business success. CSR can be adopted within company’s policies, strategies, program and commitments toward social and environment. By having social responsibilities, suppliers, business associates and customers would have more confidence in the organization and therefore, increased in sales and lead to profit maximization. The main objectives of this report are to understand the reason and the impact from the implementation of Corporate Social Responsibility activities in Standard Chartered Bank. The research methodology used to gather the information is by using primary data and secondary data.